THE HUMAN-AI INTERACTION IN ACADEMIC WRITING: A PHENOMENOLOGICAL EXPLORATION OF WRITERS' EXPERIENCES WITH CHATGPT - Nanda Ardianing Putri; Abdullah Kafabih; Amalia Salsabila Solikha; Michella Helen Cleovena; Rozanah Katrina Herda; Ana Mae M. Monteza (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2026)
The rapid development of technology, especially in artificial intelligence (AI), has led to the integration of AI tools such as ChatGPT into education. People have largely used ChatGPT as writing assistance, including for academic writing. While prior studies have examined ChatGPT in academic writing, few have explored writers’ real experiences and views from a phenomenological perspective. This study aims to investigate undergraduate and postgraduate students’ personal experiences and perspectives on the use of ChatGPT in academic writing. Using qualitative research employing a phenomenological design, this study involved four students from the English Language Education Program at one university in Yogyakarta, Indonesia. Data were collected through in-depth interviews and analyzed using Collaizi’s method to capture the essence of their experiences. The findings indicate that participants experienced ChatGPT as a productive partner in academic writing as well as a source of potential ethical, cognitive, and creative risks. However, ChatGPT raised concerns regarding excessive dependence, a decline in critical thinking, and factual accuracy. These emphasize that ChatGPT should function as a tool that assists rather than replaces writers’ intellectual contributions. This study provides insight into how academic writers’ experience the writing process with the help of AI, which can serve as a reference for educators and institutions that want to integrate AI into writing instruction.